Investigating Situational Awareness in Microblog Posts during Three Natural Disasters in the Philippines - T. VICENTE, CELESAMAE (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
During three natural disasters in the Philippines namely Typhoon Yolanda, Typhoon Glenda, and Typhoon Ruby. More specificaly this research aimed to investigate the major themes of topics and there relevance to the study events and determine the percentage of occurrence of Situational Awareness in the microblog posts when the disasters took place. Techniques used in the analysis include word frequency count, tweet relevance analysis, K means word clustering, and percentage calculation of relevant updates on Situational A wareness domains.